A Jacob/Nsmf Gene Knockout Results in Hippocampal Dysplasia and Impaired BDNF Signaling in Dendritogenesis. - Christina Spilker; Sven Nullmeier; Katarzyna M Grochowska; Anne Schumacher; Ioana Butnaru; Tamar Macharadze; Guilherme M Gomes; PingAn Yuanxiang; Gonca Bayraktar; Carolin Rodenstein; Carolin Geiseler; Angela Kolodziej; et al. (PLoS Genetics)
Jacob, the protein encoded by the Nsmf gene, is involved in synapto-nuclear signaling and docks an N-Methyl-D-Aspartate receptor (NMDAR)-derived signalosome to nuclear target sites like the transcription factor cAMP-response-element-binding protein (CREB). Several reports indicate that mutations in NSMF are related to Kallmann syndrome (KS), a neurodevelopmental disorder characterized by idiopathic hypogonadotropic hypogonadism (IHH) associated with anosmia or hyposmia. It has also been reported that a protein knockdown results in migration deficits of Gonadotropin-releasing hormone (GnRH) positive neurons from the olfactory bulb to the hypothalamus during early neuronal development. Here we show that mice that are constitutively deficient for the Nsmf gene do not present phenotypic characteristics related to KS. Instead, these mice exhibit hippocampal dysplasia with a reduced number of synapses and simplification of dendrites, reduced hippocampal long-term potentiation (LTP) at CA1 synapses and deficits in hippocampus-dependent learning. Brain-derived neurotrophic factor (BDNF) activation of CREB-activated gene expression plays a documented role in hippocampal CA1 synapse and dendrite formation. We found that BDNF induces the nuclear translocation of Jacob in an NMDAR-dependent manner in early development, which results in increased phosphorylation of CREB and enhanced CREB-dependent Bdnf gene transcription. Nsmf knockout (ko) mice show reduced hippocampal Bdnf mRNA and protein levels as well as reduced pCREB levels during dendritogenesis. Moreover, BDNF application can rescue the morphological deficits in hippocampal pyramidal neurons devoid of Jacob. Taken together, the data suggest that the absence of Jacob in early development interrupts a positive feedback loop between BDNF signaling, subsequent nuclear import of Jacob, activation of CREB and enhanced Bdnf gene transcription, ultimately leading to hippocampal dysplasia.